1991
DOI: 10.1210/endo-128-2-843
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone Overrides the Negative Effect of Reduced Dietary Energy on Gonadotropin Synthesis and Secretion in Ewes*

Abstract: During prolonged periods of reduced dietary energy, there is a reduction in secretion of LH in females. To test the hypothesis that decreased secretion of LH is due to reduced secretion of GnRH, 18 ovariectomized ewes were fed either a low-energy diet (LOW, 60% of the National Research Council recommendations, n = 12) or a normal diet, (control, n = 6), for 127 days. Each ewe received basal levels (approximately 5 pg/ml) of estradiol via sc Silastic implants. After 127 days, serum concentrations of FSH and LH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
2
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 42 publications
(29 reference statements)
3
39
2
2
Order By: Relevance
“…More recent evidence suggests that the pituitary sensitivity to GnRH pulses is decreased during undernutrition. Tatman et al (1990) found that the pituitary content of LH was lower in thin ewes; Kile et al (1991) found that undernutrition suppressed pituitary synthesis of LH, as the concentration of mRNA for both α and β subunits of LH were less in nutritionally restricted ovariectomized ewes, although pulsatile administration of GnRH was capable of restoring LH synthesis and secretion. Similarly, cows fed restricted diets released more LH in response to exogenous GnRH than cows fed moderate or high diets (Whisnant et al, 1985;Rasby et al, 1991) and had increased concentrations of GnRH in the median eminence stalk of the hypothalamus (Rasby et al, 1992), suggesting that the greater sequestration of LH in the anterior pituitary gland and decreased LH secretion in nutritionally restricted animals is because of reduced GnRH release.…”
Section: Introductionmentioning
confidence: 99%
“…More recent evidence suggests that the pituitary sensitivity to GnRH pulses is decreased during undernutrition. Tatman et al (1990) found that the pituitary content of LH was lower in thin ewes; Kile et al (1991) found that undernutrition suppressed pituitary synthesis of LH, as the concentration of mRNA for both α and β subunits of LH were less in nutritionally restricted ovariectomized ewes, although pulsatile administration of GnRH was capable of restoring LH synthesis and secretion. Similarly, cows fed restricted diets released more LH in response to exogenous GnRH than cows fed moderate or high diets (Whisnant et al, 1985;Rasby et al, 1991) and had increased concentrations of GnRH in the median eminence stalk of the hypothalamus (Rasby et al, 1992), suggesting that the greater sequestration of LH in the anterior pituitary gland and decreased LH secretion in nutritionally restricted animals is because of reduced GnRH release.…”
Section: Introductionmentioning
confidence: 99%
“…Energy restric tion or high energy expenditure results in a failure of the hypothalamo-pituitary-gonadal axis in animals [1][2][3] and in humans, being particularly prevalent in eating disor ders [4,5], Plasma levels of luteinising hormone (LH) and follicle-stimulating hormone (FSH) tend to be lower when animals such as sheep [6. 7] or humans [8] arc underfed, although such changes may depend upon whether gonads are present or absent [9,10], the macronutrient makeup of the diet [11][12][13] and the length of caloric restriction [ 14], As there is a tight coupling between pulses of gonado tropin-releasing hormone (GnRH) and LH [ 15], and since the pituitary release adequate LH in response to exoge nous GnRH in most species, including sheep, during undernutrition [2,9,[16][17][18], it is most likely that pertur bations of reproductive function are related to changes in the secretion of GnRH.…”
Section: Introductionmentioning
confidence: 99%
“…food deprivation reduces GH secretion [19] due, in part, to a reduction of GH-releasing hormone (GHRH) mRNA lev els in the hypothalamus [20]. In contrast, plasma GH levels are elevated during undernutrition in man [21], swine [22], cows [23], rabbits [24] and sheep [3,6,7], These effects on GH secretion are thought to involve altered hypothalamic function and subsequent changes in GHRH and somatos tatin (SR1H) secretion which act in concert to influence pulsatile GH patterns [25]. For instance, a reduction in SRIH secretion into the hypophysial portal vessels has been detected in ewes on a restricted diet [26].…”
Section: Introductionmentioning
confidence: 99%
“…Anestrus or amenorrhea h a s b e e n d e m o n st r a t e d t o b e c a u s e d b y nutritionally induced body weight loss in cows [4], rats [10], hamsters [11] and women [12]. In small ruminants, several studies have examined the effects of long-term restricted feeding on metabolic and hormonal environments in sheep [13][14][15]. Recently, we h a v e s u c c e s sf u l l y a d o p t e d tr a n sr e c t a l ultrasonography for monitoring the follicular and luteal dynamics during the estrous cycle in Shiba goats [16].…”
mentioning
confidence: 99%